The Role of Nurses in the Implementation of Patient Safety and Protection of Patient Rights at the Rahayu Yakkum Purwodadi Hospital - Christina Nur Widayati; Endang Wahyati Yustina; Hadi Sulistyanto (Universitas Katolik Soegijapranata Semarang, 2019)
Patient Safety was the right of a patient who was receiving health care. A nurse was one of the health professionals in a hospital having a very important role in realizing Patient Safety. In realizing Patient Safety Panti Rahayu Yakkum Hospital of Purwodadi had involved the role of the nurses. In carrying out their role the nurses could support the protection of the patient’s rights. The nurses performed health care by conducting six Patient Safety goals that were based on professional standards, service standards and codes of conduct so that the Patient Safety would be realized.This research applied a socio-legal approach to having analytical-descriptive specifications. The data used were primary and secondary those were gathered by field and literature studies. The field study was conducted by having interviews to, among others, the Director of Panti Rahayu Yakkum Hospital of Purwodadi, Head of Room and Chairman of Patient Safety Committee, nurses and patients. The data were then qualitatively analyzed.The arrangement of nurses’ role in implementing Patient Safety and the patient’s rights protection was based on the Constitution of the Republic of Indonesia of 1945, Health Act, Hospital Act, Labor Act, and Nursing Act. These bases made the hospital obliged to implement Patient Safety. The regulations leading the hospital to provide Patient Safety were Health Minister’s Regulation Nr. 11 of 2017 on Patient Safety, Statute of Panti Rahayu Yakkum Hospital of Purwodadi (Hospital ByLaws), Internal Nursing Staff ByLaws. In implementing Patient Safety Panti Rahayu Yakkum Hospital of Purwodadi had established a committee of Patient Safety team consisting of the nurses that would implement six targets of Patient Safety. Actually, the Patient Safety implementation had been accomplished but it had not been optimally done because of several factors, namely juridical, social and technical factors. The supporting factors in influencing the implementation were, among others, the establishment of the Patient Safety team that had been well socialized whereas the inhibiting factors were limitedness of time and funds to train the nurses besides the operational procedure standard (OPS) that was still less understood. Lack of learning motivation among the nurses also appeared as an inhibiting factor in understanding Patient Safety implementation.